Environmental education for hazardous waste management and risk reduction in laboratories - Tomas Rafael Pierre Martinez; Adriana Consuelo Mera (Universidad del Magdalena, 2013)
The University laboratories are places where teaching, extension and research activities are develop, which harmful substances are manipulated and hazardous waste are generated, the lack of information about this makes them an inadequate provision causing human health and environmental risks. This research proposes the implementation of environmental education as an alternative for waste management and safety in the University of Magdalena laboratories. Applying a series of polls showed the effectiveness with efficiency or assertively rises at 30% cognitive level during the process. It recommends to obtain better results is necessary evaluate the ethic component.